Acceptance of brain-computer interfaces in amyotrophic lateral sclerosis. Issue 3 (June 2015) - Geronimo, Andrew; Stephens, Helen E.; Schiff, Steven J.; Simmons, Zachary
Abstract Brain-computer interfaces (BCI) have the potential to permit patients with amyotrophic lateral sclerosis (ALS) to communicate even when locked in. Although as many as half of patients with ALS develop cognitive or behavioral dysfunction, the impact of these factors on acceptance of and ability to use a BCI has not been studied. We surveyed patients with ALS and their caregivers about BCIs used as assistive communication tools. The survey focused on the features of a BCI system, the desired end-use functions, and requirements. Functional, cognitive, and behavioral data were collected from patients and analyzed for their influence over decisions about BCI device use. Results showed that behavioral impairment was associated with decreased receptivity to the use of BCI technology. In addition, the operation of a BCI system during a pilot study altered patients' opinions of the utility of the system, generally in line with their perceived performance at controlling the device. In conclusion, these two findings have implications for the engineering design and clinical care phases of assistive device deployment.